(untitled) (Cultura Económica, 2019)
Argentina started to notice de arrival of globalization, when the concept of region had been discarded, or survived only in declarations that justified the creation of interprovincial bureaucracies. A time in which federalism was in crisis, localist impulses were arising and autarchy dreams were reflourishing. Therefore, in this country, the arrival of globalization, the failure of regionalism and the crisis of federalism were simultaneous phenomena. Once again, Argentina confronts the challenges of a changing world, without having solved its problems in the relation between the Nation and the provinces and the provinces among themselves, in the context of an agenda of national coexistence and institutional stability.